Pentecostal aesthetics : theological reflections in a pentecostal philosophy of art and aesthetics - Felix-Jager, Steven (Global Pentecostal and Charismatic studies., 2015)
Pentecostals have not sufficiently worked out a distinctively Pentecostal philosophy of art and aesthetics. In Pentecostal Aesthetics, with a foreword by Amos Yong, Steven Félix-Jäger corrects this by reflecting theologically on art and aesthetics from a global Pentecostal perspective, particularly through a pneumatic Pentecostal lens.